Environmental concentrations of fibers with fluoro-edenitic composition and population exposure in Biancavilla (Sicily, Italy) - Biagio Maria Bruni; Maria Eleonora Soggiu; Giovanni Marsili; Antonio Brancato; Marco Inglessis; Lorenzo Palumbo; Augusta Piccardi; Eleonora Beccaloni; Fabrizio Falleni; Simona Mazziotti Tagliani; Antonio Pacella (Istituto Superiore di Sanità, 2014)
INTRODUCTION. The town of Biancavilla (Sicily) was included in the National Priorities List of Contaminated Sites due to environmental dispersion of amphibole fibers owing to the extraction of materials from a local quarry. The present report summarizes results from several, hitherto unpublished, environmental surveys carried out in the area, as well as from published analyses of the chemistry and composition of fibers. METHODS. Data included here comprises environmental fiber concentrations by scanning electron microscopy with energy dispersive spectroscopy (SEM-EDS) analysis in soil, indoor and outdoor air, personal monitoring, as well as a chemical characterization of the fibers. The full chemical structure and spectroscopic characterization of fibers were obtained through a multi-analytical approach: SEM-EDS, X-ray powder diffraction (XRPD), as well as Mössbauer (MS) and Fourier transform infrared (FT-IR) spectroscopies. RESULTS. Data analyzed provided a spatial and temporal picture of fiber concentrations in Biancavilla, and a qualitative assessment of population exposure. Results suggest that until 2000, the population had been exposed to high levels of amphibole fibers. Mitigation measures adopted since 2001, gradually reduced exposure levels to about 0.10.4 ff/l. Previous studies on fibrous amphiboles from Biancavilla reported considerable chemical variability. Differences in composition, especially concerning the presence of Si, Ca, Fe, and Na, were found both within and between samples. Compared to the previously investigated prismatic fluoro-edenite, these fibrous fluorine amphiboles consistently showed higher average values of Si and Fe content, whereas Ca was significantly lower, which we consider a distinctive characteristic of the fluorine fibrous variety. CONCLUSIONS. The population of Biancavilla had been highly exposed to a suite of fibrous amphiboles for over 50 years. Dust mitigation measures have gradually reduced exposure, but continuous environmental follow-up is necessary in order to monitor exposure levels and prevent adverse health effects for future generations.